DOI: 10.31274/etd-180810-981
|View full text |Cite
|
Sign up to set email alerts
|

Summer food habits and gill raker morphology of seven Catostomid species in Iowa rivers

Abstract: Introduction Methods Results Discussion References Tables v LIST OF FIGURES CHAPTER 2. vi ACKNOWLEDGEMENTS Without the help of many people at Iowa State University my completion of this thesis would not have been possible. My major professor, Dr. Joseph Morris, and committee member, Dr. Michael Quist, both provided me with advice, equipment and always had time to visit about my research. I greatly appreciate all of the effort they put forth to help me successfully finish my project. I also thank Dr. Richard Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…Not only are invertebrates a primary component of the diet, but those consumed include a diverse array of mollusks, insects (e.g., Diptera, Ephemeroptera, Trichoptera), and crustaceans (Cahn, ; Meyer, ; Gatz, ). Recent research in Iowa on the trophic ecology of catostomids supports the observations reported by previous researchers (Spiegel, ). Given differences in the ecology of the study species, dissimilarities in habitat and the corresponding macroinvertebrate assemblage may help explain differences in growth among reaches.…”
Section: Discussionsupporting
confidence: 84%
“…Not only are invertebrates a primary component of the diet, but those consumed include a diverse array of mollusks, insects (e.g., Diptera, Ephemeroptera, Trichoptera), and crustaceans (Cahn, ; Meyer, ; Gatz, ). Recent research in Iowa on the trophic ecology of catostomids supports the observations reported by previous researchers (Spiegel, ). Given differences in the ecology of the study species, dissimilarities in habitat and the corresponding macroinvertebrate assemblage may help explain differences in growth among reaches.…”
Section: Discussionsupporting
confidence: 84%